The exploration of anti-Vibrio parahaemolyticus substances from Phellodendri Chinensis Cortex as a preservative for shrimp storage - Zheng, Huifang; Liu, Yang; Cai, Jing; Zhang, Miao; Wen, Ying; Guo, Lei (Frontiers in Microbiology, 2022)
This study aimed to optimize the ultrasonic-assisted extraction of the anti-Vibrio parahaemolyticus substances of Phellodendri Chinensis Cortex (ASPC), identify their active substances and investigate their application in shrimp storage. The ultrasonic-assisted extraction conditions of ASPC were optimized through a single-factor experiment combined with response surface methodology. The optimal parameters were the ethanol concentration of 81%, the ultrasonic power of 500 W, the temperature of 80℃, the extraction time of 23 min, and the liquid/solid ratio 25 mL/g. The antibacterial zone diameter of the obtained extract determined by agar well diffusion method was 15.56 ± 0.22 mm, which was not significantly different from the predicted value (15.92 mm). Berberine was identified as one of the main chemical components of ASPC through high-performance liquid chromatography (HPLC) combined with standard control. The minimum inhibitory concentrations of ASPC and berberine determined by tube dilution method were 0.25 and 0.03 mg/mL, respectively. The application of ASPC in shrimp storage showed that it could effectively inhibit the proliferation of V. parahaemolyticus on shrimps. This report offers good prospects for the use of Phellodendri Chinensis Cortex as a potential preservative against V. parahaemolyticus in aquatic products.